2011
DOI: 10.1111/j.1439-0418.2011.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Ginger root oil increases mating competitiveness of sterile Mediterranean fruit fly (Diptera:Tephritidae) in Western Australia

Abstract: The exposure of sterile male Mediterranean fruit fly, Ceratitis capitata (Wiedemann) to the aroma of essential oil derived from ginger root Zingiber officinale Roscoe (GRO) has been shown in field cage trials to increase their mating success. This field cage study compared the mating performance of mass reared sterile Mediterranean fruit fly males prepared for ground release programmes under four different post‐irradiation systems, two of which involved exposure of the flies to GRO aroma. In the first system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Feeding methyl eugenol not only improved the mating competitiveness of sterile male B. dorsalis , but also improved the level of egg sterility in mated wild females . Another phytochemical, ginger root oil increased mating competitiveness of sterile C. capitata and induced greater sterility to wild flies . The above findings suggests that pre‐release feeding on phytochemicals may allow for a reduction in the number of sterile flies that are produced and released due to their improved mating performance.…”
Section: Discussionmentioning
confidence: 84%
“…Feeding methyl eugenol not only improved the mating competitiveness of sterile male B. dorsalis , but also improved the level of egg sterility in mated wild females . Another phytochemical, ginger root oil increased mating competitiveness of sterile C. capitata and induced greater sterility to wild flies . The above findings suggests that pre‐release feeding on phytochemicals may allow for a reduction in the number of sterile flies that are produced and released due to their improved mating performance.…”
Section: Discussionmentioning
confidence: 84%
“…Its commercial use was hampered by expensive and impractical extraction procedures but ginger root (Zingiber officinalis Roscoe) oil has been shown to be an inexpensive alternative source of alpha-copaene (Shelly and Pahio 2002). Recently, it proved to be a male enhancing component because exposure to its aroma increases the mating success of sterile male medflies (Shelly 2001;Shelly et al 2004) and is now applied as aromatherapy to increase the competitiveness of sterile males in SIT (Shelly et al 2007;Steiner et al 2011). It also increases the competitiveness of male Natal fruit flies, Ceratitis rosa (Quilici et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of OO in protein-sugar diet were found, but no effects in the sugar-only diet Improving sterile male performance in fruit fly SIT R. Pereira et al The cost-effective GRO exposure to sterile males established and now in operational used in a number of C. capitata SIT action programmes (Shelly et al 2007b(Shelly et al ,c, 2008aParanhos et al 2008Paranhos et al , 2013JuanBlasco et al 2013;Silva et al 2013;Steiner et al 2013) sexing strains, the release of older males is preferable resulting in more flies reaching mating age in the field ) Species with longer pre-copulatory period would benefit more from longer pre-release holding periods Pereira et al 2013) Design for a fly holding system that optimizes methyl eugenol feeding and fly holding in space and time was completed for Bactrocera dorsalis. Preliminary tests on interactions of males with the semiochemical feeding structure were tested in a small-scale prototype (Tan and Tan 2013b) Comparison of males from standard conditions with males pre-conditioned to specific field conditions Pre-conditioning of sterile males to specific field conditions was assessed in Bactrocera tryoni and C. capitata for temperature Effects of cold knockdown Effect of cold knockdown varies with C. capitata density.…”
Section: Areas Addressed Main Findingsmentioning
confidence: 99%
“…Ginger root oil (GRO)-exposed males exhibit higher rates of sexual signalling compared with unexposed C. capitata males (Shelly et al 2004b(Shelly et al , 2007a(Shelly et al , 2010bPapadopoulos et al 2006;Briceñ o et al 2007;Juan-Blasco et al 2013;Paranhos et al 2013;Steiner et al 2013) GRO-exposed sterile males exhibit during sexual courtship the same wing beat duration as wild males, and this was shorter than for unexposed sterile males ) Exposure to orange oils (OO) and its components increased sexual signalling of males, and this effect was more pronounced in protein-fed C. capitata flies (Katsoyannos et al 2005;Papadopoulos et al 2006;Kouloussis et al 2013) Identification of active compounds other than GRO and their effects on sexual performance in C. capitata Exposure to fruits of five citrus species revealed that sweet oranges conferred the highest increase in male mating performance of C. capitata males. Exposures to commercial citrus oils were found to be similarly effective Positive effect of OO components (limonene, b-myrcene, and linalool) was found in protein/sugar-fed males, but not in sugar-only-fed males A mixture of limonene, b-myrcene, linalool, a-pinene and geraniol (1:1:1:1:1) was proven to be very effective for both wild and sterile C. capitata males ) Attractiveness of GRO and OO to C. rosa…”
Section: Areas Addressed Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation